NOS1AP Is a Genetic Modifier of the Long-QT Syndrome - Crotti, Lia; Monti, Maria Cristina; Insolia, Roberto; Peljto, Anna; Goosen, Althea; Brink, Paul A.; Greenberg, David A.; Schwartz, Peter J.; George, Alfred L. (Circulation (New York, N.Y.), 2009)
Background— In congenital long-QT syndrome (LQTS), a genetically heterogeneous disorder that predisposes to sudden cardiac death, genetic factors other than the primary mutation may modify the probability of life-threatening events. Recent evidence indicates that common variants in NOS1AP are associated with the QT-interval duration in the general population. Methods and Results— We tested the hypothesis that common variants in NOS1AP modify the risk of clinical manifestations and the degree of QT-interval prolongation in a South African LQTS population (500 subjects, 205 mutation carriers) segregating a founder mutation in KCNQ1 (A341V) using a family-based association analysis. NOS1AP variants were significantly associated with the occurrence of symptoms (rs4657139, P =0.019; rs16847548, P =0.003), with clinical severity, as manifested by a greater probability for cardiac arrest and sudden death (rs4657139, P =0.028; rs16847548, P =0.014), and with greater likelihood of having a QT interval in the top 40% of values among all mutation carriers (rs4657139, P =0.03; rs16847548, P =0.03). Conclusions— These findings indicate that NOS1AP , a gene first identified as affecting the QTc interval in a general population, also influences sudden death risk in subjects with LQTS. The association of NOS1AP genetic variants with risk for life-threatening arrhythmias suggests that this gene is a genetic modifier of LQTS, and this knowledge may be clinically useful for risk stratification for patients with this disease, after validation in other LQTS populations.